Deep Vein Thrombosis and Pulmonary Embolism: Two Complications of COVID-19 Pneumonia? - Poggiali, Erika (Eur J Case Rep Intern Med, 2020)
Coronavirus disease 19 (COVID-19) is a worldwide infection which was recently declared a global health emergency by the WHO Emergency Committee. The most common symptoms are fever and cough, which can progress to pneumonia, acute respiratory distress syndrome (ARDS) and/or end-organ failure. Risk factors associated with ARDS and death are older age, comorbidities (e.g., hypertension, diabetes, hyperlipidaemia), neutrophilia, and organ and coagulation dysfunction. Disseminated intravascular coagulation and coagulopathy can contribute to death. Anticoagulant treatment is associated with decreased mortality in severe COVID-19 pneumonia. In this report we describe two patients with COVID-19 pneumonia who developed venous thromboembolism. LEARNING POINTS: Deep vein thrombosis and pulmonary embolism can occur in patients with COVID-19 pneumonia. Low-molecular-weight heparin prophylaxis does not decrease the risk of venous thromboembolism (VTE) in COVID-19 pneumonia. In the presence of clinical signs and/or suspicion of VTE, compression ultrasound and echocardiography should be always performed, irrespective of disease stage.